The Epystimology of Islamic Jurisprudence on Covid-19 Vaccine in Indonesia - Fateh, Mohammad; Islamy, Athoillah (Jurnal Hukum Islam, 2021)
The Covid-19 vaccination program in Indonesia, practically has received a pro and contra in the society. In this context, the Majelis Ulama Indonesia (MUI) came through its fatwa to respond the contra-productive of the community over the succession of the vaccination program. This study analysis the epistemological basis of Islamic law in the construction of the MUI Fatwa Number. 02 of 2021 about Covid-19 Vaccine Products from Sinovac Life Sciences Co. Ltd. China And Pt. Bio Farma (Persero). This qualitative research used philosophical approach, statute approach and conceptual approach. The results show, the epistemological construction of the MUI fatwa No. 02 of 2021 about the Covid-19 vaccine, Sinovac tends to integrate the paradigm of idealism and realism of Islamic law. The tendency of the integrative paradigm can be seen from the epistemological basis of the MUI fatwa formulation on the halalness of the Sinovac Covid-19 vaccine, which is normative-deductive and empirical-inductive, beside that still use preventive fiqh rules (sad al-dhariah) and benefit (maslahatul mursalah) as the basis for formulating a fatwa. This conclusion can be seen in various elements in the epistemological construction of the MUI Fatwa. First, universal ethical moral values ('am) are taken from the texts (al-Qur'an and Hadith). Second, several fiqh rules emphasize the sadd al-zari'ah (preventive action) and maslahah mursalah (public benefit). Third, the opinion of classical scholars. Fourth, the thought of experts regarding the Covid-19 vaccine.